MICROCONTROLLER IMPLEMENTATION ON ULTRASONIC SENSOR BASED AUTOMATIC TRASH CAN SYSTEM - Wanayumini, Wanayumini; Isnaini, Fitri; lvindra, Farhan A; Wardana, Revo (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2024)
Abstract : Waste management in Sei Beluru Village faces challenges due to population growth and increasing waste volume. This research aims to design and implement an automatic waste bin system based on microcontroller using Arduino Uno. The research uses experimental method with hardware and software development stages including system design, component integration, and testing. The developed system integrates HCSR-04 sensors for waste volume detection, infrared sensors for object presence detection, and servo motors for automatic opening-closing mechanism. Test results show that the system successfully detects waste levels with high accuracy and operates the opening-closing mechanism effectively. The implementation of this system proves effective in optimizing waste management in Sei Beluru Village by reducing physical interaction and preventing waste accumulation. Keywords : arduino uno; HCSR-04 sensor; automatic waste bin; HCSR-04 sensor; microcontroller; waste management.  Abstract : Waste management in Sei Beluru Village faces challenges due to population growth and increasing waste volume. This research aims to design and implement an automatic waste bin system based on microcontroller using Arduino Uno. The research uses experimental method with hardware and software development stages including system design, component integration, and testing. The developed system integrates HCSR-04 sensors for waste volume detection, infrared sensors for object presence detection, and servo motors for automatic opening-closing mechanism. Test results show that the system successfully detects waste levels with high accuracy and operates the opening-closing mechanism effectively. The implementation of this system proves effective in optimizing waste management in Sei Beluru Village by reducing physical interaction and preventing waste accumulation. Keywords : arduino uno; HCSR-04 sensor; automatic waste bin; HCSR-04 sensor; microcontroller; waste management.